2019
DOI: 10.14746/amup.9788323234098
|View full text |Cite
|
Sign up to set email alerts
|

Polskie badanie EU Kids Online 2018 Najważniejsze wyniki i wnioski

Abstract: Nota metodologiczna Tabela 1.2. Charakterystyka badanej próby ze względu na płeć i grupy wiekowe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 46 publications
0
12
0
4
Order By: Relevance
“…Moreover, almost 19.2% of students knew only about some of the technical security issues in particular they define the awareness of hacker attacks and viruses; 11% of students were aware that they cannot be sure who they are talking to on the Internet. Another research conducted in 2018 revealed that almost 19% of primary school students during the year had viruses or other malware on their ICTs (Pyżalski et al, 2019). One-fourth of young people admitted that they had met an adult they met on the Internet: 39% of them informed their parents about it, and 29%-no one (NASK, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, almost 19.2% of students knew only about some of the technical security issues in particular they define the awareness of hacker attacks and viruses; 11% of students were aware that they cannot be sure who they are talking to on the Internet. Another research conducted in 2018 revealed that almost 19% of primary school students during the year had viruses or other malware on their ICTs (Pyżalski et al, 2019). One-fourth of young people admitted that they had met an adult they met on the Internet: 39% of them informed their parents about it, and 29%-no one (NASK, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Effective prevention of "traditional" threats of cyberspace requires shaping skills useful in evaluating one's own behaviour in a long-term perspective and going beyond simple actions violating norms. The proposed research model related to piracy, values and time orientation is also useful for addressing other e-threats, such as cyberbullying, cyberaggression, identity theft, and sexting among others [42].…”
Section: Discussionmentioning
confidence: 99%
“…Namely, low and average levels of PIU severity was found in two-thirds of the students (66%), the results of every third adolescents (31.8%) indicated high levels and the remaining 2.2% a very high levels of PIU indicators. On the other hand, the report on the "EU Kids Online 2018" survey, which used Young's criteria (seven PIU symptoms), indicates that the cumulative daily prevalence of PIU symptoms among 11-to-17year-old adolescents (N = 985) was 4.7% for two, 1.6% for three, 1.1% for four, and less than 0.5% for five or more symptoms [40]. At the same time, the vast majority of respondents (82.4%) did not declare the daily presence of any PIU symptoms, and less than every tenth teenager confirmed only one symptom (9.2%).…”
Section: Prevalencementioning
confidence: 99%
“…Mianowicie niski i przeciętny poziom nasilenia PUI stwierdzono u 2/3 badanych (66%), wyniki co trzeciego nastolatka (31,8%) wskazywały na wysoki poziom, a pozostałe 2,2% na bardzo wysoki poziom natężenia wskaźników PUI. Z kolei w raporcie z badania "EU Kids Online 2018", które korzystało z kryteriów Young (siedem symptomów PUI), czytamy, że skumulowane codzienne występowanie symptomów PUI wśród młodzieży w wieku 11-17 lat (N = 985) wynosiło 4,7% dla dwóch symptomów, 1,6% dla trzech, 1,1% dla czterech oraz poniżej 0,5% dla pięciu lub więcej symptomów [40]. Przy czym zdecydowana większość badanych (82,4%) nie zadeklarowała codziennego występowania żadnego z symptomów PUI, a niespełna co dziesiąty nastolatek potwierdzał tylko jeden symptom (9,2%).…”
Section: Impact Of Covid-19 Pandemicunclassified